Comparison of Efficacy and Safety of Leptin Replacement Therapy in Moderately and Severely Hypoleptinemic Patients with Familial Partial Lipodystrophy of the Dunnigan Variety - Simha, Vinaya (Endocrine Society, 2012)
CONTEXT: Leptin replacement therapy improves metabolic complications in patients with lipodystrophy and severe hypoleptinemia (SH), but whether the response is related to the degree of hypoleptinemia remains unclear. OBJECTIVE: The aim of the study was to compare efficacy of leptin therapy in familial partial lipodystrophy, Dunnigan variety (FPLD) patients with SH (serum leptin <7th percentile of normal) vs. those with moderate hypoleptinemia (MH; serum leptin in 7th to 20th percentiles). DESIGN, SETTING, AND PATIENTS: We conducted an open-label, parallel group, observational study in 14 SH (mean ± sd, serum leptin, 1.9 ± 1.1 ng/ml) and 10 MH (serum leptin, 5.3 ± 1.0 ng/ml) women with FPLD. INTERVENTION: Patients received 0.08 mg/kg · d of metreleptin by twice daily sc injections for 6 months. MAIN OUTCOME MEASURES: The primary outcome variable was change in fasting serum triglycerides. Other secondary variables were fasting plasma glucose and insulin, insulin sensitivity, hemoglobin A1c, and hepatic triglyceride content. RESULTS: Median fasting serum triglycerides decreased from 228 to 183 mg/dl in the SH group (P = 0.04) and from 423 to 339 mg/dl in the MH group (P = 0.02), but with no difference between the groups (P value for interaction = 0.96). Hepatic triglyceride levels similarly declined significantly from 8.8 to 4.9% in the SH group and from 23.7 to 9.2% in the MH group (P value for interaction = 0.9). Loss of body weight and body fat occurred in both groups. Fasting glucose, insulin, glucose tolerance, and hemoglobin A1c levels did not change. K value on insulin tolerance test improved slightly in the SH group (0.98 to 1.24%; P = 0.01), but not in the MH group (1.1 to 1.27%; P = 0.4). CONCLUSION: Metreleptin replacement therapy is equally effective in FPLD patients with both SH and MH in reducing serum and hepatic triglyceride levels, but did not improve hyperglycemia.